Depression, anxiety, and stress in medical students in Peru: a cross-sectional study - Valladares-Garrido, Danai; Quiroga-Castañeda, Pedro P.; Berrios-Villegas, Iván; Zila-Velasque, J. Pierre; Anchay-Zuloeta, Claudia; Chumán-Sánchez, Marisella; Vera-Ponce, Víctor J.; Pereira-Victorio, César J.; Failoc-Rojas, Virgilio E.; Díaz-Vélez, Cristian; Valladares-Garrido, Mario J. (Frontiers in Psychiatry, 2023)
Objective: To determine the prevalence and factors associated with depressive, anxious, and stress symptoms in medical students in Peru, during the second pandemic wave of COVID-19. Methods: We conducted an analytical cross-sectional study in 405 medical students from a university in northern Peru.The DASS-21 instrument was used to evaluate mental health outcomes (depression, anxiety, and stress), and to investigate their association with socio-educational characteristics. Results: We found a prevalence of depressive, anxious, and stress symptoms of 71.6% (95% CI: 66.94-75.95), 71.9% (95% CI: 67.2-76.2), and 62.7% (95% CI: 57.8-67.4); respectively. Students with eating behavior disorders had a higher prevalence of depressive symptoms (PR:1.35), anxious symptoms (PR:1.27), and stress symptoms (PR:1.31). The prevalence of depressive symptoms (PR: 1.57), anxious symptoms (PR: 1.27), and stress symptoms (PR: 1.24) increased in students who did not report regular physical activity. In addition, having almost always academic exhaustion increased the prevalence of depressive symptoms (PR:1.46), stress symptoms (PR: 1.72). On the contrary, the prevalence of depressive symptoms (PR: 0.79), anxious symptoms (PR: 0.73) and stress symptoms (PR: 0.82) decreased in male students. Students who reported sleeping 8 or more hours daily had a lower prevalence of stress symptoms (PR: 0.82).Conclussion: Symptoms of depression and anxiety occurred in 7 out of 10 students, and stress in 6 out of 10. Among the factors associated with the presence of anxiety, depression, and stress were eating behavior disorder and not regularly exercising. Periodic evaluations of mental symptomatology are required and counseling should be promoted in medical schools.